AGEING POPULATION PERCEPTIONS ON EXPECTED LEARNING CONTENTS AND AGEING-CENTERED MODES IN THE SIX GEO-POLITICAL ZONES OF NIGERIA - Aminu Kazeem Ibrahim (Indonesian Journal of Learning and Instruction, 2020)
The purpose of the study is to determine perceptions of ageing population on preferred learning contents and modes towards possible consideration into existing adult life-long open education curriculum in Nigeria. The method involves descriptive, cross-sectional survey design with 378 adult retirees. Data collection instrument was, Ageing Perceived Learning Contents and Modes Scale’. Percentages and t – test statistic was used to analyse the data. The results indicated 61.90 years as mean age, perceived learning contents were, activities for group with specific knowledge and abilities (59=15.61%); preventing security threat (71=18.78%); modalities for starting a petty trading and skill acquisitions (51=13.49%); diverse family and community roles (41=10.85%); ageing social and health care (65=17.19%); changes in legislations and policies (43=11.38%) and favoured learning modes indicated, life-long open education and learning for adult later life (39=10.32%); use of technological innovations (59=15.61%); consideration of gender, culture and economic status (121=32.01%). The result also discovered a significant gender difference on preferred learning contents (t = 4.69 < 2.101) and learning modes (t = 2.91< 1.957) among participants. The study concluded that dynamic of ageing preferred learning contents and modes calls for consideration on exiting adult life-long open education curriculum in Nigeria and other similar areas.Keywords: ageing population; learning contents; ageing-centered learning modes.